Cardiac Myxoma- 17 Years Experience in a Tertiary Care Centre of Bangladesh (Bangladesh Heart Journal, 2018)
Cardiac Myxoma is the most common benign intracardiac tumor of heart. We studied its incidence, clinical presentations, short term outcome, morbidity and mortality following surgery over a period of 17 years. The study was performed inthe department of cardiac surgery, National institute of Cadiovascular diseases (NICVD) Dhaka, over a period from 2000to 2016. NICVD is the tertiary hospital for cardiovascular surgery in the Government sector. Over this period of 17 years 11,923 open heart surgery was done of which 129 were cardiac myxoma patients. As a result, cardiac myxoma patients constituted 1.08%of all open heart surgery. Preoperative diagnosis was done on clinical presentations and 2D echocardiography, which is the most important tool for its diagnosis. Most of the patients presented at 4th to 5th decade of life. The patients presented with triad ofvalve obstructive features, embolic symptoms andconstitutional symptoms alone or in combination. Among all myxoma patients, majority(86.6%) had left atrial myxoma. Cardiac myxoma forms a very small percentage of all cardiac diseases requiring surgical treatment. Immediate surgical excision is indicated in all patients to avoid life-threatening complications. Outcome of surgical treatment was excellent.Bangladesh Heart Journal 2017; 32(2) : 85-88